(untitled) (Research, Society and Development, 2021)
Objetive: Develop a high-fat diet (HFD) model that standing alone did not develop the Non-alcoholic fatty liver disease (NAFLD), allowing one to study the association of comorbidities with the high-fat diet model. Material and methods: The rats were divided into 2 groups: standard diet and high-fat diet, each group with 8 animals. The rats were submitted to the analysis of the following parameters in hepatic tissue: dosage of malondialdehyde (MDA), glutathione (GSH) and myeloperoxidase activity (MPO). Liver samples were also assessed histopathologically for serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), alkaline phosphatase (FAL), uric acid and total cholesterol (TC), calcium (CA), urea and HDL. Results: The results showed that there was a significant difference in MDA, GSH, total cholesterol (CT), ALT, ALB, uric acid (AU), calcium (CA) and HDL. The histopathological evaluation presented a low score, insufficient for the classification of NAFLD. Conclusion: This study demonstrated that the high-fat diet model did not cause NAFLD. This finding allows one to use the high-fat diet characterized in this study to investigate the possible hepatic alterations caused by other comorbidities.